Chicken - Machin, Freddie ca. 20. Jh; Linden, Tom ca. 20. Jh (Network, 2017)
"The powerful feature-film debut of acclaimed young director Joe Stephenson, this compelling coming-of-age drama [...] Richard, a fifteen-year-old boy with learning difficulties who lives in a shabby caravan with his older brother, Polly. Life for Richard is harsh, with the engaging, nature-loving teenager yearning for stability while frequently finding himself on the wrong side of his brother's destructive, often violent moods. Finding it easier to communicate with animals none more so than his beloved hen, Fiona Richard nevertheless forms a friendship with rebellious seventeen-year-old Annabel, whose family have recently acquired the farmland on which the brothers live. But growing conflict with the new landowners will lead to a situation that severely tests Richard's natural optimism, as a world of privilege collides with the brothers' precarious, marginalised existence." [amazon.co/uk]
Original: Großbritannien 2015
Bildformat 2.35:1
Special features: Ian McKellen interviews Scott Chambers ; "Hatching Chicken" ; Morgan Watkins audition ; trailer and TV spot ; phone videos ; Scott Chambers monologue ; full score ; extensive image galleries
Keywords: Film; DVD-Video